Strategi Pemasaran Dalam Penjualan Produk Tabungan Pada PT Bank Muamalat KCP Stabat - Lisa, Azhar, Khairani Sakdiah (Jurnal Pusat Studi Pendidikan Rakyat, 2022)
As the largest Islamic Bank in Indonesia, PT. Bank Muamalat KCP Stabat is here to provide several products to help the needs of its customers. These products range from funding products, financing products and other banking services. One of the funding products that complements the Mabrur Savings product is PT. Bank Muamalat KCP Stabat also launched Mabrur Junior Savings or known as children's haj savings. Mabrur Junior Savings is a funding facility provided by PT. Bank Muamalat KCP Stabat to assist customers in carrying out the Hajj pilgrimage who find it difficult to determine the long waiting time. This type of research is field research (Field Research), which is descriptive qualitative. The data sources for this research were obtained from primary data sources and secondary data sources using interviews and documentation techniques that aim to describe the marketing strategy for Mabrur Junior Savings products carried out by PT. Bank Muamalat KCP Stabat. The data analysis used in this study is a qualitative analysis method, because the data obtained is in the form of descriptions or statements obtained from interviews with the Sharia Funding Executive, Customer Service and three customers of PT. Bank Muamalat KCP Stabat. The results of this study indicate that the marketing strategy implemented by PT. Bank Muamalat KCP Stabat on the Mabrur Junior Savings product, namely by implementing the four elements contained in the marketing mix or Marketing Mix, namely Product Strategy, Price Strategy, Place Strategy, and Promotion Strategy, even though there are obstacles in its implementation. The marketing strategy for Mabrur Junior Savings products from 2020 to 2023 has increased but not significantly. Preferably PT. Bank Muamalat KCP Stabat further enhances the marketing of its products by providing rewards and additional facilities in order to attract savings and operate more effectively.